Bisphenol A in utero induced glutamate and D-serine metabolic dysregulation in the hippocampus of rats and primary cultured astrocytes - Luxin Zhang; Xinran Li; Yichen Zhao; Panjie Wang; Mengwenhui Shi; Xiao Li; Xiucong Pei; Zhiwen Duan; Mingyue Ma; Haiyang Yu (Ecotoxicology and Environmental Safety)
Bisphenol A (BPA) is a widely used synthetic compound that could cause neurobehavioral abnormalities in mammals. Previous studies have suggested that NMDAR may be a potential target of BPA-induced neurotoxicity. However, the impact of exposure to BPA on glutamate (Glu) and D-serine (D-ser) metabolism (key regulators of NMDAR activation) has not been clarified yet. Pregnant SD rats were exposed to 0, 0.05, 0.5, 5 and 50 mg/kg/day BPA via oral gavage from gestational day (GD) 5 to GD 19, and primary cultured astrocytes (AS) from neonatal rats were exposed to 5, 10 and 20 μmol/L BPA, respectively. Neurochemical experiments were conducted to investigate dysfunctions in Glu and D-ser metabolism both in the hippocampus of rats’ offspring at different developmental stages and in AS. Results showed that BPA exposure in utero induced Glu accumulation and inhibited GS, GLS1, and GDH expression and activity at the gene, protein, and enzymatic levels in the hippocampus of rats’ offspring during different developmental stages (GD 20, PND 21, and PND 56). However, BPA exposure in utero increased D-ser levels at GD 20 but decreased them from PND 21 onward. Additionally, BPA exposure in utero inhibited SR, asc-1, and ASCT2 expression, while promoting ASCT1 expression during these stages. Besides, BPA exposure in utero up-regulated DAAO expression at GD 20 but down-regulated it from PND 21 onward. Moreover, BPA exposure inhibited the expression and activity of GS (except for its expression), GLS1, and GDH, while suppressing SR and DAAO expression but increasing ASCT2 expression without altering ASCT21 expression in AS. These findings will provide new insights into the pathogenesis of BPA-induced neurotoxicity through Glu and D-ser metabolic pathways.